Pengaruh Kemampuan Pemecahan Masalah Matematis Terhadap Hasil Belajar Siswa Sekolah Menengah Kejuruan (SMK) - Ananda Safitri; Attin Warmi; Hanifah Hanifah (Mandalika Mathematics and Educations Journal, 2026)
This research was conducted due to the low mathematical problem-solving ability on the mathematics learning outcomes of Vocational High School (SMK) students which are not optimal. The purpose of this study is to analyze the influence of mathematical problem-solving ability on student learning outcomes. The approach in this study uses quantitative with a population of all grade XI students of SMKS Bina Karya 2 Karawang, totaling 103 students, and 26 students as a sample determined through a purposive sampling technique. Essay tests to measure mathematical problem-solving ability and Mid-Semester Test (UTS) scores are the instruments used as indicators of learning outcomes. Data were analyzed through normality tests, linearity tests, and simple linear regression analysis. The study shows that mathematical problem-solving ability has a positive and significant influence on student learning outcomes, with a significance value of 0.000 (<0.05) and a regression equation of Y = 5.342 + 0.596X. The amount of contribution given reaches 45%, which indicates that this ability is one of the important factors in improving learning outcomes, although there are still other factors that play a role.